Effects of sodium hydrogen sulfide (a H2S donor) on acute kidney injury - Esrafil Mansouri (Society of Diabetic Nephropathy Prevention, 2018)
Implication for health policy/practice/research/medical education: Hydrogen sulfide plays an important role in renal pathology and shows the protective role under pathological conditions in some of experimental models of renal disease.